2006
DOI: 10.1002/chem.200600154
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐Phase Protonation and Deprotonation of Acrylonitrile Derivatives NCCHCHX (X=CH3, NH2, PH2, SiH3)

Abstract: A combined experimental and theoretical study on the gas-phase basicity and acidity of a series of cyanovinyl derivatives is presented. The gas-phase basicities and acidities of (N[triple chemical bond]C--CH==CH--X, X=CH(3), NH(2)) were obtained by means of Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometry techniques. The corresponding calculated values were obtained at the G3B3 level of theory. The effects of exchanging CH(3) for SiH(3), and NH(2) for PH(2), were analyzed at the same level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Our results (see Table S5 of the Supporting Information) indicate that reaction (6) is 80 kJ mol À1 more exothermic than reaction (7). This means that the S N 2 nucleophilic substitution is thermodynamically favored over the deprotonation process.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Our results (see Table S5 of the Supporting Information) indicate that reaction (6) is 80 kJ mol À1 more exothermic than reaction (7). This means that the S N 2 nucleophilic substitution is thermodynamically favored over the deprotonation process.…”
mentioning
confidence: 59%
“…As a consequence, a great deal of effort was concentrated on determining intrinsic reactivities, in particular intrinsic basicities and acidities. [2][3][4][5] The gas-phase acidity of phosphines has been reported [6,7] and the role played by the substituent on the acidity of the molecule clearly evidenced. In particular the presence of an a,b-unsaturated substituent [6] with or without an electronwithdrawing group [5,7] led to a huge increase in acidity.…”
Section: Introductionmentioning
confidence: 95%
“…By comparison the increase in PA from propionitrile to butyronitrile is equal to 4 kJ/mol only (Table ). It may be suggested that the large increase in PA value observed for CH 3 CH═CHCN is associated with an efficient hypercongugative effect of the methyl group with the C═C unsaturated moiety of the protonated form …”
Section: Unsaturated Cyanidesmentioning
confidence: 84%
“…Amino acrylonitrile itself, NH 2 CH=CHCN, has been the subject of several studies . This compound may be obtained by reaction of ammonia on cyanoacetylene as a Z:E mixture close to 1 in condensed phase .…”
Section: Nitrogen Substituted Cyanidesmentioning
confidence: 99%
“…The corresponding E isomeric ion is much more stable than the Z-one, so that only the former should be found in the gas-phase. For the basicity, push-pull effects explain the preference of aminoacrylonitrile to protonate at the cyano group, which also explain the relatively high basicity of this derivative as compared to the other members of the set analyzed, which present rather similar gas-phase basicities: GB ≈ 780 kJ mol −1 , indicating that the different nature of the substituents has a weak effect on the intrinsic basicity of the cyano group [51]. This push-pull effect was also observed by photoelectron spectroscopy [52].…”
Section: Adducts Of Cyanoacetylenementioning
confidence: 84%